responda a expressão abaixo:
a)
![\sqrt{16} + \sqrt{36} = \sqrt{16} + \sqrt{36} =](https://tex.z-dn.net/?f=+%5Csqrt%7B16%7D+%2B++%5Csqrt%7B36%7D++%3D+)
b)
![\sqrt{25} + \sqrt{9} = \sqrt{25} + \sqrt{9} =](https://tex.z-dn.net/?f=+%5Csqrt%7B25%7D++%2B++%5Csqrt%7B9%7D++%3D+)
c)
![\sqrt{49} - \sqrt{4} = \sqrt{49} - \sqrt{4} =](https://tex.z-dn.net/?f=+%5Csqrt%7B49%7D++-++%5Csqrt%7B4%7D++%3D+)
Soluções para a tarefa
Respondido por
12
Resposta:
a 4+6= 10
b 5+ 3= 8
c 7-2=5
obs √16=4 √36=6 √25=5 √9=3 √49=7 √4=2
Explicação:
espero que tenha ajudado muito
Kaickbraynperreira:
desculpa
Perguntas interessantes
Matemática,
9 meses atrás
Saúde,
9 meses atrás
Português,
9 meses atrás
Português,
1 ano atrás
Informática,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás